Pengaruh Debt Default, Pertumbuhan Perusahaan, dan Solvabilitas terhadap Opini Audit Going Concern - Mhd. Husein Pasaribu; Riva Ubar Harahap (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Annual financial statements are a means of publication that can be used by every business management in informing the company's financial condition to interested parties, this is certainly needed to create transparency between business management and stakeholders in the community, including matters related to the receipt of going concern audit opinions issued by independent auditors. The purpose of this study is to analyze what factors can influence the going concern audit opinion seen in terms of debt default, company growth, and solvency owned by a company. With a sample of 26 companies engaged in property and real estate listed on the Indonesia Stock Exchange (IDX), this study will use a quantitative-associative approach with the analytical technique used is logistic regression analysis that utilizes supporting tools in the form of statistical software in the form of SPSS. This study will use time-series data where the period of years to be observed is from 2019 to 2021, thus the amount of data to be processed and analyzed will total 78 raw data. The results obtained in this study included 26 companies sampled in the study, 19 of which received a going concern audit opinion with determinants that influence it, including: 1) Debt default has no effect on the going concern audit opinion (significance value 0.196 (greater than 0.05)); 2) Company growth has no effect on the going concern audit opinion (significance value 0.646 (greater than 0.05)); and 3) Solvency affects the going concern audit opinion (significance value 0.023 (less than 0.05)). In addition, if analyzed together, the three determinants still do not show a significant influence on the going concern audit opinion variable, it can be seen from the significance value of 0.055 (greater than 0.05) in companies engaged in property and real estate listed on the IDX.